2013
DOI: 10.1093/ndt/gft272
|View full text |Cite
|
Sign up to set email alerts
|

The value of repeat biopsy in the management of lupus nephritis: an international multicentre study in a large cohort of patients

Abstract: The histopathological data suggest that morphological differences between segmental and global forms do exist, possibly due to different pathogenetic mechanisms. An RB strategy could provide additional information on long-term renal outcomes. A strategy of protocol biopsies could be useful in perspective future trials to better understand the therapeutic response and the natural history of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 23 publications
3
38
0
2
Order By: Relevance
“…As shown by other studies [8,9,22,23] , we found persistent histopathological renal activity despite apparent clinical response. Furthermore, PL in repeated RB was associated with more frequent and early risk of renal flare.…”
Section: Discussionsupporting
confidence: 89%
“…As shown by other studies [8,9,22,23] , we found persistent histopathological renal activity despite apparent clinical response. Furthermore, PL in repeated RB was associated with more frequent and early risk of renal flare.…”
Section: Discussionsupporting
confidence: 89%
“…[1,3,5] However, data from the literature do not seem to confirm this approach. [4,68,70,71,74,75] Although the proliferative classes were the majority in the reference biopsy in nearly all of the reviewed series (484/676; 72%), the results of the repeat biopsy led to a change in the immunosuppressive treatment in 18% to 79% of the patients (mean 57% of cases), intensifying it in the majority of the cases (between 18% and 60.5%; mean 39%). These data suggest that in daily clinical practice, in some cases with clear progression of proliferative lesions in the second biopsy despite the initial treatment, the immunosuppressive treatment was intensified to avoid the progression of renal damage and the development of sclerosing lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our series, as well as the literature review, confirm that histological transformation is very prevalent during an LN flare, ranging from 40% to 76% of cases, [6876] and supports the usefulness of a repeat biopsy in guiding treatment of LN flares, both to identify those patients for whom it is necessary to intensify immunosuppression therapy and to avoid unnecessary increased immunosuppression therapy in others. [4,68,70,71,7375] However, the frequency of histological transformation and the clinical value of repeat biopsy vary greatly depending on the LN class from the initial biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…A high rate of transformations to another histological class was observed in reports in which a repeat biopsy was performed for various reasons [71,83], (Table 4). However, no clinical predictor of transformation has been identified [81,84].…”
Section: How Often Should Renal Biopsy Be Performed?mentioning
confidence: 95%